Kasus Temuan Produk Obat dan Makanan Ilegal Yang Dijual Melalui E-Commerce dan Korelasinya dengan Peraturan Badan Pengawas Obat dan Makanan Nomor 8 Tahun 2020 - Nissa Hanum; Siti Nafisa; Siti Rohmah; Yumareta Anggun Nihan; Elvira Julia Ariyanto (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2024)
Background: The advancement of information and communication technology has led society to rely on the use of communication devices and the internet. The global increase in e-commerce, coupled with the growth of digital health services, provides direct access to healthcare for patients, as well as globalization of production and distribution of medications. However, it is important to note that these activities can become illegal if e-commerce actors or involved institutions lack the necessary business permits and fail to comply with certification, licensing, registration, and other legal requirements. Aim: This article explores findings of illegal drug products within the context of online drug circulation through e-commerce. Method: The approach employed in this research is qualitative, utilizing descriptive analysis methods and data collection techniques through literature review. Result: It has been revealed that the sale of illegal drugs online occurs on the Marketplace through accounts using official pharmacy names. The illegal drugs and food products discovered do not adhere to good manufacturing standards and have unknown dosages. This poses a serious risk to public health if consumed. The identified types of illegal products include drugs specifically for men, illegal weight loss products, fake health supplements, illegal cosmetics, and counterfeit processed foods. Conclusion: The misuse of e-commerce platforms for the sale of illegal products must be taken seriously to safeguard the health and overall safety of the public. Keywords:  Illegal drugs, Online distribution, Supervision, Prevention, Legality